CAN BLUE LASER IMAGING COLLABORATE IN THE DIFFERENTIAL DIAGNOSIS BETWEEN NEOPLASTIC AND NON-NEOPLASTIC COLORECTAL LESIONS? - Santos, Carlos Eduardo Oliveira dos (2023)
Introduction: Improved endoscopic imaging allows the differential diagnosis of colorectal lesions in real time through the study of the microvasculature. Objective: To review the use of Blue Laser Imaging (BLI) in analyzing the capillary patern for the differential diagnosis between neoplastic and non-neoplastic lesions. Method: This is an integrative review of the literature that collected information published on virtual platforms in Portuguese and English. The search for reading and analysis was carried out on the SciELO – Scientific Electronic Library Online, Google Scholar, Pubmed and Scopus platforms. The descriptors taken from DeCS/MESH were: “Blue laser imaging. Endoscopy. Chromoendoscopy, Colorectal polyps. Magnification” and its English counterparts “Blue laser imaging. Image-enhanced endoscopy. Chromoendoscopy. Colorectal polyps. Magnification” with AND or OR search, considering the title and/or abstract. Only those that had the greatest correlation to the topic were included, and the review was based on them, with reading, in full, of the texts. Results: In the end, 22 articles resulted that made up this review. Conclusion: BLI associated with magnification showed good results in real-time predictive histological diagnosis for colon and rectal lesions.